Impact of Watershed Programme On Groundwater and Surface Water Development - Prakash, Om; Sastry, G.; Reddy, Y.V.R. (Journal of Soil and Water Conservation, 2022)
Preliminary survey was conducted in thirty-seven watersheds under different agro- ecosystem regions during 2000-2001 to gather information on the changing status of surface water, ground water, runoff, soil erosion and damage to various soil and water conservation structures constructed in the watersheds. Ground water table has risen up by 0.1 to 2.6 m and surface water availability has increased by 1 to 41 per cent. Reduction in runoff varied from 10 to 45 per cent due to various measures. The reduction in soil erosion varied from 10 to 50 per cent. Damages to soil conservation and water harvesting structures varied from 5 to 80% except at one location (Ralegoan Siddhi watershed) where there was negligible damage. The status of various parameters was represented through histograms and statistical analysis was done to calculate mean, standard deviation and coefficient of variation of the parameters institution-wise and agro-ecosystem region-wise.